PENGARUH VARIASI TEMPERATUR NORMALIZING TERHADAP BESAR BUTIR DAN KEKERASAN MATERIAL BAJA KARBON AISI 1035 - Suhardan Suhardan; R Kohar (Jurnal Turbulen, 2019)
Mechanical properties of steel do not only depend to its chemical composition but also its micro structure. This mechanical property can be modified with heat treatment processes, one of them is by using normalizing method. This process is able to manipulate both micro structure and particle size. In order to investigate the influence of Normalizing temperature, An AISI 1035 steel is treated by Normalizing with various temperatures from 820 to 880 ⁰C. Since each sample is treated by same method, the microstructure of each sample is also similar. In addition the difference variation of normalizing temperature among each sample causes the variation of grain size. The increasing of temperature Normalizing causes the increasing of its grain size. The influence of of grain size is investigated by doing Rockwell Hardness Test. Based on the result, steel which has bigger grain size has higher hardness property. Keywords: : Mechanical Characteristics, Micro Structure, Normalizing, Grain Size